An Analysis of Students Error In Solving PISA 2012 And Its Scaffolding - Yurizka Melia Sari; Erik Valentino (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2016)
Based on PISA survey in 2012, Indonesia was only placed on 64 out of 65 participating countries. The survey suggest that the students’ ability of reasoning, spatial orientation, and problem solving are lower compare with other participants countries, especially in Shouth East Asia. Nevertheless, the result of PISA does not elicit clearly on the students’ inability in solving PISA problem such as the location and the types of student’s errors. Therefore, analyzing students’ error in solving PISA problem would be essential countermeasure to help the students in solving mathematics problems and to develop scaffolding. Based on the data analysis, it is found that there are 5 types of error which is made by the subject. They consist of reading error, comprehension error, transformation error, process skill error, and encoding error. The most common mistake that subject do is encoding error with a percentage of 26%. While reading is the fewest errors made by the subjects that is only 12%. The types of given scaffolding was explaining the problem carefully and making a summary of new words and find the meaning of them, restructuring problem-solving strategies and reviewing the results of the completion of the problem.